LUDIC APPROACH TO TEACH ITALIAN AS FOREIGN LANGUAGE (FL) - Aida GJINALI; Manjola ÇULLHAJ (International Journal of Social and Educational Innovation)
This research aims to highlight how necessary and important is to apply the ludic approach as a teaching tool in teaching a foreign language.  The use of the ludic approach in language classes is fundamental to create not only a playful, stimulating, and motivating atmosphere, but above all because, as the literature already points out, the game is fundamental for spontaneous and motivating learning.